Physiological effects of dietary complex carbohydrates and its metabolites role in certain diseases - Khattak, Muhammad Muzaffar Ali Khan (Asian Network for Scientific Information, 2002)
Carbohydrate is one of the basic and an important food nutrient consumed worldwide. Like-wise Pakistani foods contain more carbohydrates than any other food nutrient consumed. Sometimes, Pakistani foods are devoid of protein and may contain only carbohydrates and fats as the major nutrients of the diet e.g. eating chapati (wheat bread) with potato curry. Certain non-communicable diseases can be avoided with adoption of proper healthier food habits and eating foods according to the needs of the body. These diseases are obesity, coronary heart disease, colonic cancer and gastrointestinal disorders (diverticular disease, constipation, hiatal hernia and hemorrhoids). Therefore complex carbohydrate should be an important constituent of our daily meal and it can be adopted for the management of certain diseases provided that it is used in proper amounts. Consumption of certain complex carbohydrates is associated with lower body weight, reduced blood cholesterol, reduced blood glucose and an increased crypt cell proliferation. Therefore, it is necessary and utmost important to know the various types of carbohydrates to enable us to decide to include carbohydrates in our daily food according to our health requirements. Not necessarily all the community need to know but at least those who are associated with nutrition and health management must know the beneficial as well as the harmful effects of carbohydrates.